Survei Tingkat Religiusitas Siswa - Hiyya Ichsania; Heri Saptadi Ismanto; Rahmawati Hidayat (Guidance : Jurnal Bimbingan dan Konseling, 2023)
This study aims to provide an explanation of the level of religiosity of students which currently shows a number of problems among adolescents that occur due to a lack of independence in religious aspects. This research is a type of survey research with a quantitative approach. The population in this study was class XI KJIJ SMK Negeri 7 Semarang which consisted of two classes. The research sample of 36 students was determined through a saturated sample. The level of religiosity is presented based on indicators. Based on the results of data analysis according to predetermined category intervals, it shows that all indicators of the level of student religiosity show scores in the High category, even though the criteria for indicators of religious experience students show lower results than the achievements on other indicators such as indicators of belief, religious practice, religious appreciation and religious knowledge.